The Utilization of Smartphones in Learning Media on Social Studies at SMPN 13 Banjarmasin - Rusmaniah Rusmaniah; M. Ridha Ilhami; Nursahid Nursahid; Jumriani Jumriani; Muhammad Rezky Noor Handy (Universitas Lambung Mangkurat, 2023)
The development of information technology today has reached all aspects of people's lives. Currently, the form of information technology application that is in great demand by the public is a smartphone. Technology has an important role in everyday life and uses it in various aspects of life, for example today many are using technology in learning to find information about work with smartphones. Social studies teachers at SMP Negeri 13 Banjarmasin in general still apply conventional learning methods in the process of teaching and learning activities. Conventional methods and media provided by teachers in learning can be seen when teachers only use whiteboards as learning media and lecture methods or simple discussions in teaching and learning activities. This study used qualitative research methods. This method is used to understand and describe phenomena that occur in the field, namely at SMP Negeri 13 Banjarmasin. in this way can explain in depth what happened in the field by using the method of observation, interviews, and documentation. The reason teachers are unable to develop instructional media, especially using smartphones, is because of their limited ability in the field of computer technology and assume that developing instructional media is a time-consuming and complicated activity. There are various uses of smartphones by social studies teachers such as smartphones as a tool for finding learning media, smartphones as a tool for accessing online learning media, and smartphones as a tool for developing learning media. So that learning that takes place using technological media is very supportive of learning and is something that is needed in increasing students' learning interest.